2018
DOI: 10.2478/jaes-2018-0011
|View full text |Cite
|
Sign up to set email alerts
|

Ranking of Effects of Construction Delay: Evidence from Malaysian Building Projects

Abstract: The problem of delay is a regular phenomenon in construction projects all around the world and the Malaysian building projects has no exclusion. The aim of this paper is to determine and rank the effects of delay in Malaysian building projects with respect to their Relative Importance Index. Literature review and questionnaire survey were used to gather data for this study. A thorough literature review was performed to identify the common effects of delays in building construction projects. A questionnaire was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 13 publications
1
12
0
Order By: Relevance
“…2, the top 10 effects of delay in Algerian construction project were: 1) Time overrun: all the three parts agreed to classify 'time overrun' as the first most important effect with an importance index of 4.14; when projects are delayed, more days of work is required to finish the execution of the project, as a result, the prescribed delivery time is extended and the project is said to have experienced time overrun [19,41]. This result was supported by various researches [1,3,15,24,28,30,31,33,35,37,39,41,45] in which 'time overrun' was the first most important effect of delay.…”
Section: Evaluation Of the Effects Of Delaymentioning
confidence: 81%
See 2 more Smart Citations
“…2, the top 10 effects of delay in Algerian construction project were: 1) Time overrun: all the three parts agreed to classify 'time overrun' as the first most important effect with an importance index of 4.14; when projects are delayed, more days of work is required to finish the execution of the project, as a result, the prescribed delivery time is extended and the project is said to have experienced time overrun [19,41]. This result was supported by various researches [1,3,15,24,28,30,31,33,35,37,39,41,45] in which 'time overrun' was the first most important effect of delay.…”
Section: Evaluation Of the Effects Of Delaymentioning
confidence: 81%
“…The collected data were analysed using the relative importance index (RII) as stated by many researchers [3,17,23,24,25,31,30,39,45] an RII N  …”
Section: Analytical Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…Construction firms in Indonesia implemented 20 factors of ISO in 2012 to improve the construction process and results. Those important factors of ISO 9001 include; design control system, quality system, process control, purchasing, product availability, inspection, contract review, management responsibilities, controlling for quality control, mitigation measure for internal and external causes and handling, external and internal quality audit, a system of controlling nonconforming products, statistical techniques, storing, control documentation and data, testing and measuring of performance of equipment, servicing, training, packing and preservation of material, system for customer-supplied products [10][11].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The delays in the delivery of work contracts still appear as a recurring issue in engineering projects, which often occur from design to completion, whether in public or private works, in developing or developed countries. The consequences are disputes and litigation between the parties, cost escalation, loss of profit, poor service quality, arbitrage, overrun of the deadline defined for executing the works or closing the project (AKOGBE;FENG;ZHOU, 2013;DOLAGE;PATHMARAJAH, 2015;GONZÁLEZ et al, 2014;GUNDUZ;OZDEMIR, 2015;KHAN;GUL, 2017;EL-RASAS, 2014;SWEIS, 2008;ULLAH et al, 2018). It is further observed that the delays in construction projects is a fact observed globally or on a large scale, affecting not only the industry itself, but the economy of nations in general; thus negatively impacting the success of the project due to changes in the original execution schedule and the previously established costs, quality criteria and management of safety conditions (CHAUHAN; SHAH; RAO, 2008;DORAISAMY;AKASAH;YUNUS, 2020;FARIDI;EL-SAYEGH, 2006;FLYVBJERG et al, 2002;MYDIN et al, 2014a).…”
Section: Introductionmentioning
confidence: 99%